2019
DOI: 10.17707/agricultforest.65.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Populus Caspica and Populus Alba Cuttings Under Different Irrigation Intervals

Abstract: Understanding the function of poplar species under different irrigation regimes is critical for water resources and ecosystem sustainable management. This study was conducted in order to understand the performance (survival and height growth) of two poplar species (Populus alba L. and Populus caspica Bornm.) cuttings in two lengths (15 cm and 25 cm) under three irrigation treatments (7-day, 14-day and 21-day intervals). One trial was established using split-split-plot design with three replications. Every two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In general, the mean values of these parameters were higher in plants under a 12-day irrigation interval, with little or no difference between the 3-day and 6-day irrigation intervals (Figures 7 and 8). ISSN 2166-0379 2020 ISSN 2166-0379 2020 accumulation, tend to be negatively affected by longer irrigation intervals, given the less frequent water supply (Bagheri et al, 2012;Asadi and Alimohamadi, 2019). In this study, however, lower values of plant height and total dry mass were found in 3-day and 6-day irrigation intervals, compared to 12-day interval.…”
Section: Journal Of Agricultural Studiescontrasting
confidence: 46%
“…In general, the mean values of these parameters were higher in plants under a 12-day irrigation interval, with little or no difference between the 3-day and 6-day irrigation intervals (Figures 7 and 8). ISSN 2166-0379 2020 ISSN 2166-0379 2020 accumulation, tend to be negatively affected by longer irrigation intervals, given the less frequent water supply (Bagheri et al, 2012;Asadi and Alimohamadi, 2019). In this study, however, lower values of plant height and total dry mass were found in 3-day and 6-day irrigation intervals, compared to 12-day interval.…”
Section: Journal Of Agricultural Studiescontrasting
confidence: 46%
“…This fact could have forced trees in Plot 3 to invest more in root development. However, trees in Plot 1 could reach water closer to the soil surface, therefore releasing biomass to invest in height growth, as it has been proven in other plantations [43][44][45]. All this plot-level variability in growing conditions has caused a high variability in tree height among trees of the same age.…”
Section: Simplified Volume and Height Equationsmentioning
confidence: 97%